Integration of 3D objects in an augmented reality flashcard game as an innovation in cognitive learning media at Salafiyah Comal Kindergarten - Khusnul Alfiana Azizah; Dicky Anggriawan Nugroho; Mohammad Irsyad; Lulu Nisaul Wakhidah (Universitas Negeri Yogyakarta, 2026)
Learning at Salafiyah Comal Kindergarten is still dominated by conventional media, which provide limited visual stimulation and direct interaction, resulting in suboptimal child engagement. Although augmented reality has the potential to enhance interactivity, the development of AR flashcard media integrated with 3D objects and interactive quizzes for early childhood remains limited. Therefore, this study aims to develop an AR-based flashcard game media with a “transportation” theme and to test its feasibility among children aged 4–5 years. The method used is Research and Development (R&D) following the ADDIE model, involving 16 children. The media was developed using Assembler Edu with the integration of flashcards, 3D objects, and interactive quizzes. Validation results showed the media had an 80% feasibility rating in the “Good” category, and the content received a 95.5% rating in the “Very Good” category. Additionally, the media implementation received a 92.75% response rate in the “Very Good” category. These three assessments indicate that the media possesses a sufficiently high level of feasibility and is suitable for practical use as an interactive learning tool to support children’s engagement in the learning process. The application of AR showed that children were more active, interested, and engaged in the learning process. Therefore, the developed media is suitable for use as an interactive learning medium to support engagement and cognitive stimulation. Further research is recommended to test the media’s effectiveness in enhancing cognitive development using a broader experimental design and a larger sample size.